Development of Design of Light Strike Vehicle and Analysis with Different Ballistic Materials - B. Madhu Gangadhar, A. Charan Sai Teja, D. Ajay Kumar, G. Ramakrishna, B. Harsha Vardhan, K. Hemanth Kumar (International Journal of Advanced Science and Technology, 2020)
“Light Strike Vehicle” (LSV) is an ameliorated version of the “Desert Patrol Vehicle” (DPV) it replaced. It is also known as “Light Attack Vehicle”. It consists of weapons at Elevated Rear central of the vehicle. Although some countries have replaced their DPVs instead of Humvees in their military force, special operation groups embraced the Light Strike Vehicle for its compact size and high mobility. It is used for fast hit and run style raids, scouting missions and Special Forces support. General “Light Strike Vehicle” (LSV) is entirely un-armoured and it doesn’t offer any protection from small arms fire. In this project, we are developing the design of the vehicle with Armor’s and to increase the stability of the vehicle while a weapon attack during the war. So, we are performed analysis on “ANSYS workbench” with different Ballistic materials whether the selective materials are suitable for the vehicle during attacking mode